Current Scenario of Heart Diseases in Nepal: At a glance - Shakya, S; Sharma, D; Bhatta, YD (Nepalese Heart Journal, 2013)
Background Cardiovascular disease no more remains as a disease of developed countries. It is affecting developing countries as well. In addition, developing countries have big challenge to deal with these because of lack of resources and lack of studies related to it. This study is an attempt to portrait a picture of cardiovascular problems in Nepal on the basis of records obtained in various cardiac camps conducted by Shahid Gangalal National Heart Center in September 2008 to July 2011. Methods and materials The reports of 19 cardiac camps were analyzed. Result The proportion of congenital heart disease in cardiac camps ranges from 0.35% (Dolakha) to 5.04% (Dhangadi). The proportion of RHD ranges from 3.25% (Bhaktapur) to 30.67% (Dhangadi). The proportion of hypertension ranges from 5.11% (Dolakha) to 39.41% (Baglung). The proportion of CAD ranges from 0.56% (Tikapur) to 15.12% (Birgunj). Conclusion The proportion of CHD and RHD were found the highest in Dhangadi. The lowest proportion of hypertension was found in Dolakha, the study was conducted in Singati, which is the most remote area among the areas included in this study. The highest proportion of hypertension was found in Baglung. The highest proportion of Coronary artery disease was found in Birgunj. In every camp, the hypertension claims the major proportion of cardiovascular problem. It reflects, Nepal is in a rising epidemic of coronary artery disease. Preventive programs should be emphasized sooner as possible to prevent catastrophic effect of Cardiovascular Disease in Nepal. DOI: http://dx.doi.org/10.3126/njh.v8i1.8333 Nepalese Heart Journal Vol.8(1) 2011 pp.23-26